Reconstructing Fiqh in Post-Reform Indonesia: From Theocentric to Anthropocentric Paradigms - Muhammad Fikri Adrian; Zeni Ayu Ariani (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2025)
This study investigates the transformation of Islamic law (fiqh) discourse in post-Reformation Indonesia, highlighting the intellectual shift that emerged following the democratization process in 1998. While previous research has described the general openness of this period, this study identifies and analyzes the novel patterns of legal reasoning and methodological renewal that distinguish contemporary Indonesian fiqh. Employing qualitative content analysis of key literature, including scholarly books, journal articles, and dissertations, this study uncovers how the increased intellectual freedom has enabled scholars to develop more context-sensitive interpretations of Islamic law. The study’s main contribution lies in its systematic mapping of post-Reformation fiqh trends, particularly the rise of anthropocentric and socially responsive Islamic law. These findings reveal that, despite facing resistance from traditionalist perspectives, this evolving discourse marks a significant epistemological shift that aligns Islamic legal thought more closely with the needs of modern plural societies.